Organizational structure impacts on project performance among worker at oil and gas industry - Nur Aqilah, Jamaludin (2015)
The aim of this research is to study organizational structure and project performance. For the organizational structure as the independent variable. Then, project performance of as the dependent variable. Eighty respondents from the oil and gas industry in Kuala Lumpur were surveyed by questionnaire. The collected data were analyzed by using SPSS software which used the method of Cronbach’s Alpha (reliability analysis), correlation analysis, regression analysis and descriptive statistics. The objectives of this study is to determine the effectiveness of organization structure to project performance and to identify the relationship between organization structures with project performance. The results of study is show that there is a significant positive relationship between organizational structure and project performance.